Development of PeduliLindungi Application Features Using Design Thinking - Lila Setiyani; Inpresta Natali; Jasmine Fitriyah Yamani (Politeknik Piksi Ganesha Indonesia, 2023)
The PeduliLindungi app has supported the government in controlling the spread of COVID-19. The purpose of this research is to explore new user needs and create design prototypes for the latest features of the PeduliLindungi application. Design thinking is used to know empathizing, define, ideate, and prototype. Figma Tools was chosen to develop a prototype that visualizes the latest features of the PeduliLindungi application. The results of this research are information about pain points from application users, problem statements, problem solving ideas, and user interface features for the new PeduliLindungi application. Based on the results of user pain points, the features developed are covid-19 event advertisements, Online Registration, Night Mode, Covid-19 educational videos, Tourist Visits, and Vaccine History. Based on the evaluation results using the Single Easy Question (SEQ), it is found that advertising, registration, night mode, and vaccine history are worth 7, meaning that the level of use is basic to use. Tourist visits and educational videos are worth 5.75, which means that improvements need to be made by taking into account notes from respondents during the testing process.